EVALUATION OF THE IMPLEMENTATION OF ACTIVE FIRE PROTECTION SYSTEM AT ERNALDI BAHAR SUMATERA SELATAN - Titi Nurhaliza; Desheila Andarini; Poppy Fujianti; Dwi Septiawati; Mona Lestari (Dian Nuswantoro Semarang, 2021)
Introduction: The hospital is a place that is quite prone to fire hazards. Ernaldi Bahar has various characteristics of activities that have the potential to cause fires such as medical and administrative activities that use electrical installations as well as the use of intensive fire sources in kitchens, laundry or generator rooms as well as the presence of relatively high burning materials sourced from various medicines, chemicals, LPG gas cylinders and oxygen. The purpose of the research is to evaluate the implementation of active fire protection system at Ernaldi Bahar. Methods: This study uses qualitative methods with observational approaches, interviews and document studies. Result: The results showed that the active fire protection system at Ernaldi Bahar Hospital is well categorized with a percentage of 69% value with the results of fire alarm analysis based on Kepmen PU No.10 Year 2000, NFPA 72 and SNI 03-3985-2000 (81%), fire detector analysis based on NFPA 2000 and SNI 03-3985-2000 (100%), apar analysis based on NFPA 10 (89%), building hydrant analysis based on Permen PU No.26 Year 2008 and SNI 03-1745-2000 (73%), analysis of page hydrants based on Permen PU No.26 Year 2008 and SNI 03-1745-2000 (73%), and Sprinkler analysis based on SNI 03-3989-2000 (0%). Conclusion: Active fire protection system has been implemented well with a percentage of 69% value but it need some improvement in maintenance, placement, recording and completeness of active fire protection system components. Keywords: Hospital, Fire, Active Fire Protection System